A polydopamine-enabled approach towards core-shell nanoparticles with multifunctionality - Hoo, Hsing Yi (2016)
This report provides an overview of a strategic way to synthesize plasmonic core-shell nanoparticles that has a certain distance between the different layers in the nanoparticles. The different layers of the core-shell nanoparticles are separated by the mussels-inspired polydopamine (PDA), where the thickness of the spacer can be tuned by varying the amount of PDA. The redox active properties exhibited by PDA also enhanced the growth of the metal shell in the nanoparticles. Besides using metal nanoparticles as the core of these structure, other types of materials such as magnetic nanoparticles were used to form multifunctional hybrid nanoparticles and to determine whether PDA is applicable to other kind of materials as coating and spacer. The plasmonic core-shell nanoparticles has a broad spectrum of optical properties and the structural integration opens up more opportunity in applications like theranostics and catalysis.